2018
DOI: 10.17576/ajag-2018-09-12
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effect of culture on the relationship between women directors and CSR disclosure in Malaysia

Abstract: This study examines the moderating effect of culture on the relationship between women directors and CSR disclosure. The reason for examining this issue is twofold. First, the effort and focus to improve the representation of women on corporate boards in Malaysia is continually being discussed since 2011. Thus, having women on corporate boards may affect company's CSR disclosure differently if compared to when boards are dominated by men. Second, having multiethnic boards may also influence the decision-making… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In the case of the present study, in terms of the year of publication, four articles were published in 2020 (Jamil et al, 2020;Abdullah et al, 2020;Janang et al, 2020;Md Zaini et al, 2020); four articles were published in 2019 (Chang et al, 2019;San Ong et al, 2019;Alazzani et al, 2019;and Ismail & Latiff, 2019); seven articles were published in 2018 (Mohamed Adnan et al, 2018;Yusoff et al, 2018;Hamzah & Abdullah, 2018;Abd Rahman & Ku Ismail, 2018;Ismail et al, 2018;Said et al, 2018;Talpur et al, 2018); and two articles were published in 2017 (Sadou et al, 2017;Wahab et al, 2017).…”
Section: General Findings and Background Of The Studies Included In The Reviewmentioning
confidence: 52%
See 2 more Smart Citations
“…In the case of the present study, in terms of the year of publication, four articles were published in 2020 (Jamil et al, 2020;Abdullah et al, 2020;Janang et al, 2020;Md Zaini et al, 2020); four articles were published in 2019 (Chang et al, 2019;San Ong et al, 2019;Alazzani et al, 2019;and Ismail & Latiff, 2019); seven articles were published in 2018 (Mohamed Adnan et al, 2018;Yusoff et al, 2018;Hamzah & Abdullah, 2018;Abd Rahman & Ku Ismail, 2018;Ismail et al, 2018;Said et al, 2018;Talpur et al, 2018); and two articles were published in 2017 (Sadou et al, 2017;Wahab et al, 2017).…”
Section: General Findings and Background Of The Studies Included In The Reviewmentioning
confidence: 52%
“…More specifically, it should be noted that a total number of eight studies included ownership structure as the factor that affects voluntary disclosure, environmental disclosure and CSR disclosure (Zaini et al, 2020;Chang et al, 2019;Ong et al, 2019;Alazzani et al, 2019;Mohamed Adnan et al, 2018;Ismail et al, 2018;Said et al, 2018;Sadou et al, 2017). The board of directors' characteristics were examined by nine studies (Jamil et al, 2020;Janang et al, 2020;San Ong et al, 2019;Alazzani et al, 2019;Ismail & Latiff, 2019;Mohamed Adnan et al, 2018;Abd Rahman & Ku Ismail, 2018;Said et al, 2018;Sadou et al, 2017). Financial performance was examined by five studies (Abdullah et al, 2020;Yusoff et al, 2018;Sadou et al, 2017;Wahab et al, 2017).…”
Section: General Findings and Background Of The Studies Included In The Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In supporting this business claim, Adams and Ferreira (2009) found diverse boards to be more diligent in monitoring management. In fact, a recent study in Malaysia by Rahman and Ismail (2018) found women directors to positively influence CSR disclosure and there were attempts by Sahari et al (2018) to develop human rights index disclosure where the prospect for women's role might be more pronounced.…”
Section: Introductionmentioning
confidence: 99%
“…Corporations were asked to show greater concern and community responsibility. The implementation of CSR in public banking companies in Malaysia has succeeded in integrating stakeholder interests as the company's goal of earning profit but still paying attention to aspects of sustainable social and environmental responsibility and company commitments that pay attention to non-financial aspects (Jaiyeoba et al, 2018;Jusoh & Ibrahim, 2018;Jie & Hasan, 2018;Rahman & Ismail, 2018). Several dimensions of organizational strategy applied by Malaysian banking public companies in the successful CSR implementation are Visibility, Voluntarism, Proactivity, Specificity and Centrality.…”
Section: Introductionmentioning
confidence: 99%